A hard kick in the nuts : what I've learned from a lifetime of terrible decisions - Steve-O, 1974-; Peisner, David; Glover, Stephen (Hachette Books, 2022)
"Stephen "Steve-O" Glover--social media icon, comedy-touring stalwart, and star of Jackass--delivers a hilarious and practical guide to recovery, relationships, career, and how to keep thriving long after you should be dead. Steve-O is best known for his wildly dangerous, foolish, painful, embarrassing, and sometimes death-defying stunts. At age 48, however, he faces his greatest challenge yet: getting older. A Hard Kick in the Nuts: What I've Learned from a Lifetime of Terrible Decisions is a captivating exploration of life and how to live it by an individual who has already lived way more than a lifetime's worth of extreme experiences. Steve-O grapples with the right balance between maturity and staying true to yourself, not repeating your "greatest hits," maintaining sobriety and a healthy regimen, avoiding selfishness, and finding the right partner for life. Having built a gargantuan and loyal social media following while establishing a successful stand-up career--all after a couple of decades of dubious behavior--Steve-O is proof that anyone can find meaning and fulfillment in life, no matter what path they choose. Packed with self-deprecating wit and gruelingly earned wisdom, A Hard Kick in the Nuts will reverberate with readers everywhere who have lived a lot (sometimes too much) and are now wondering how to approach the years to come. Or maybe just need some good motivation to get out of bed tomorrow. One of many tips: Be your own harshest critic, then cut yourself a break, and enjoy this book"--